The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.31219/osf.io/vn7x6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 prevention and control measures in workplace settings: a rapid review and meta-analysis

Abstract: Workplaces are high-risk environments for SARS-CoV-2 outbreaks and subsequent community transmission. Identifying, understanding, and implementing effective workplace SARS-CoV-2 infection prevention and control (IPC) measures is critical to protect workers, their families, and communities. A rapid review and meta-analysis were conducted to synthesize evidence assessing the effectiveness of COVID-19 IPC measures implemented in global workplace settings through April 2021. Medline, Embase, PubMed, and Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
2
30
0
2
Order By: Relevance
“…It is likely that longer exposure and high viral concentration during working hours could be underlying factors in the development of more severe COVID-19 symptoms. In fact, it has been reported that preventive measures against COVID-19 were less strict during 2021 compared to those in 2020 [19] as well as that wearing only face masks at the workplace might not be sufficient to be fully protected [20], which could be applicable in places where the students were employed in the past summer. Toward the end of the summer break, fewer students reported holiday travel.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that longer exposure and high viral concentration during working hours could be underlying factors in the development of more severe COVID-19 symptoms. In fact, it has been reported that preventive measures against COVID-19 were less strict during 2021 compared to those in 2020 [19] as well as that wearing only face masks at the workplace might not be sufficient to be fully protected [20], which could be applicable in places where the students were employed in the past summer. Toward the end of the summer break, fewer students reported holiday travel.…”
Section: Discussionmentioning
confidence: 99%
“…Survey items on universal testing, contact tracing, vaccinations, and signage did not t into the 9-domain model. However -because research shows the ability of universal testing and timely contact tracing to prevent COVID-19 outbreaks (5); that the rollout of vaccines plays a crucial part in protecting workers (32); and that COVID-19 training should be reinforced by the use of signage placed in strategic locations (33) -each of these items were considered important for content validity and left in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…From February to April 2019, the researchers conducted an extensive review of relevant research literature and meta-analysis to investigate the effectiveness of measures to prevent and control COVID-19 outbreaks in global workplace settings. Results of this review identi ed that combinations of (1) basic preventive measures (i.e., masking, hand hygiene, and social distancing), (2) surveillance measures, (3) outbreak investigations and response, (4) environmental adjustments, and (5) education initiatives can effectively prevent workplace outbreaks (5). These categories became the framework for the development of a survey allowing researchers to measure the level of occupational COVID-19 protection available to workers from diverse geographic and occupational settings.…”
Section: Creating the Surveymentioning
confidence: 99%
See 2 more Smart Citations